Mengkritisi Putusan Mahkamah Konstitusi Tentang Penetapan Tersangka Sebagai Objek Praperadilan: Criticizing the Constitutional Court’s Decision Regarding Determining Suspects as Pretrial Objects - Mahmud Mulyadi (Asosiasi Pengajar Hukum Pidana dan Kriminologi Indonesia (ASPERHUPIKI), 2024)
The Constitutional Court (MK) decision number 21/PUU-XII/2014, dated 28 April 2015 has expanded the determination of suspect status as one of the pre-trial objects. This has had consequences in law enforcement, namely a shift in the nature of pretrial examination from the formal aspect to the material aspect (validity testing), and there is a vacuum in formal law in the Indonesian Criminal Procedure Law. This decision is felt to be inappropriate because